Enhancing the Business Tourism Infrastructure in Uzbekistan - Turayev Baxodir Xotamovich; Samiyev Siroj Saitovich (Indonesian Journal of Law and Economics Review, 2020)
This article is devoted to the study of problems of business tourism development in the Republic of Uzbekistan. Moreover, the ways of development of infrastructure and improvement of activity of tourist organizations in this direction are considered